The impact of published school performance results on residential property prices: a comparative study of two UK cities. (21st June 2011) - Nellis, Joseph G.; Glen, John
This paper presents a study which examines the relationship between published school performance results and house prices in two UK cities. It is postulated that schools which perform better on the most widely recognised measure of performance become oversubscribed and give preference to children living in close proximity to their school. Parents wishing to obtain access to such schools then seek to move to the 'catchment' area for those schools, bidding up house prices in those areas. We develop a hedonic price model which relates the price of a house to the physical characteristics of the property, the nature of the local area in which the property is situated and to the key measure of performance of the nearest school. We test this model using a large dataset and find that there is a positive correlation between this performance measure and house prices.